Numerical simulation of condensation in a minichannel - Zhao, Huanyu (Nanyang Technological University, 2022)
An air-cooled condenser is an important type of heat exchanger used in many industry fields. As manufacturing techniques develop, the minichannel condenser shows great potential in the heat transfer performance. In this dissertation, condensation heat transfer in a minichannel has been investigated by numerical simulation. The diameter of the minichannel is 1 mm and the refrigerant used is R134a. The software used is Ansys Fluent. A literature review of multi-phase flow and heat transfer sets the background for the models investigated. The simulation is performed for steady state condensation heat transfer. The Volume of Fluid (VOF) model is used to capture the interface while the − ω (SST) model is used to simplify the turbulence. The Lee model is used for the liquid-vapour mass transfer process. The coefficient of the Lee model is set to 10000. A pressure-based solver is used for equation-solving. Three inlet values of the mass flux are set in separated cases, viz., 100 kg /m2∙ s, 150 kg /m2∙ s, and 300 kg /m2∙ s. The condensation heat transfer coefficients are compared with experimental data and correlations. The accuracy of the model has been validated. The heat transfer coefficient decreases as the vapour quality decreases. The tube with a larger mass flux has larger heat transfer coefficient. The liquid film profile is compared with theoretical models in the literature. The numerical model considered the effect of surface tension and gravity. The interface between the liquid and vapour in the thin film layer is much smaller than the interface in the accumulated layer. The temperature field and velocity fields are also analysed. The temperature of the liquid phase is much lower than the saturation temperature. A large variation in the temperature difference occurs at the interface. The velocity of the liquid phase is also much lower than the vapour phase. A growing velocity boundary layer exists in the vapour phase.